Catalytic Investigation of NiCl2(PPh3)2 in Hidrogenation, Cross-Coupling, Oligomerization, and Isomerization Reactions - SARI SINAMBELA 10513060, NOVITA
The NiCl2(PPh3)2 complex was employed on various organic reactions, i.e. oligomerization of ethylene, olefin modification with alkyl halide, pinene isomerization, and furfural hydrogenation. The Ni(II) complex was synthesized according to reported literatures, i.e. by reacting NiCl2.6H2O and PPh3 in ethanol at 65 oC for 30 minutes. The complex was characterized by XRD, MSB, and MS. The Ni(II) was reduced to Ni(0) complex by addition of Zn powder as a reducing agent. The complex was observed to be active in a hydrogenation reaction of furfuraldehyde to furfuryl alcohol. This catalyst was selective towards carbonyl, but not to olefin of furfural. Catalytic tests on hydrogenation of furfural were conducted at various temperature (25, 80, 100, 120, and 140 oC). Variation of phosphine additives (PPh3, OPPh3, P(Ph-pMe)3, P(Ph-pOMe)3) and nickel salts were conducted at 80 oC. The hydrogenation reaction took place only when Ni(II) had been reduced to Ni(0). Furfuryl alcohol of 21% was generated from furfural when reaction was conducted at 80 oC for 5 hours. The further hydrogenation of furfuryl alcohol to tetrahydrofurfurylalcohol does not proceed on the typical condition. However, reaction of furfural with ethanol solvent produced an acetal by-product. All the catalytic reaction result were characterized using 1H-NMR and GC.